Liver Transplantation in Patients with Acute-onChronic Liver Failure: Challenging the Limits - Juan Manuel Diaz; Ezequiel Mauro; Maria Nelly Gutierrez-Acevedo; Adrian Gadano; Sebastian Marciano (European Medical Journal, 2021)
Acute-on-chronic liver failure (ACLF) is one of the main causes of death on the waiting list. Liver transplantation (LT) is the only curative treatment for patients with ACLF and therefore it should be considered in all cases. However, the applicability of LT in patients with ACLF is challenging, given the scarcity of donors and the high short-term mortality of these patients. Organ allocation has traditionally been prioritised according to the model for end-stage liver disease (MELD) system. However, the accuracy of MELD score is limited in patients with ACLF. In this article, the authors review the outcomes of patients with ACLF before and after LT, highlighting its clinical course, the feasibility of LT in the sickest patients, the role of the organ allocation system, and possible indicators of futility.